(untitled) (Journal of Informatics Education and Research, 2025)
This paper looks at how consumer laws affect women’s financial freedom and how they are affected by them. It shows how important legal rights are for empowering women financially. Consumer rules, which are meant to protect people from unfair business practices, make it harder for women to get involved in the financial markets and become financially independent. Even though things have improved, women still have a lot of money problems, such as unequal pay, trouble getting loans, and being treated unfairly in the job market. This study looks at important customer safety laws, like job, credit, and anti-discrimination laws, and how they have affected women’s ability to make money. There is a focus on specific legal changes that have helped women’s economic results and case studies are used to show how consumer laws can either help or hurt their financial security. The study also shows that these laws need to be enforced more strictly and cultural and social hurdles that keep women from being financially independent need to be taken down. The last part of the paper makes policy suggestions for how to improve consumer rules, help women learn about money, and get more women involved in making economic decisions. Overall, the study shows how important consumer rules are for giving women financial power and promoting equality between men and women in the workplace.